1997
DOI: 10.1007/s004600050176
|View full text |Cite
|
Sign up to set email alerts
|

Production and characterization of thermally-annealed large clusters by high-pressure laser-vaporization technique

Abstract: We have developed a high-pressure laser-vaporization cluster source, which enables us to produce large, annealed clusters. Large carbon clusters up to C + 2000 , annealed sodium fluoride clusters of Na + (NaF) n , and ammonium iodide clusters of NH + 4 (NH 4 I) n have been produced by this technique. Annealed ammonium iodide clusters show a transition from hydrogen bonded complexes to ionic crystals as the cluster size increases. The characterization of the present technique and the production processes of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1997
1997
2000
2000

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…However, Boweres and coworkers have found that these carbon clusters are not actually fullerenes; they evolve from carbon clusters to fullerenes by annealing [2,3]. We have also found that the annealing process is essential for production of fullerenes and other clusters that should have perfect structures [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 88%
“…However, Boweres and coworkers have found that these carbon clusters are not actually fullerenes; they evolve from carbon clusters to fullerenes by annealing [2,3]. We have also found that the annealing process is essential for production of fullerenes and other clusters that should have perfect structures [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 88%